Eosinophilic airway inflammation and eosinophilic chronic rhinosinusitis during nivolumab and ipilimumab. Issue 7 (30th July 2020) - Watanabe, Hirofumi; Asada, Kazuhiro; Shirai, Toshihiro; Torii, Hiroko; Yoshimura, Koji; Kusafuka, Kimihide
Abstract: Immune‐related adverse events (irAEs) are induced by immune checkpoint inhibitors (ICIs) which are administered for many cancers. There are many irAEs such as endocrine abnormalities, interstitial lung disease, and colitis. However, irAEs associated with type 2 (T2) inflammation are less known. We herein report a 71‐year‐old woman who developed eosinophilic airway inflammation and eosinophilic chronic rhinosinusitis (ECRS) simultaneously during combination therapy with nivolumab and ipilimumab for renal cell carcinoma. After two cycles of therapy, she developed cough and nasal congestion with high level of fractioned exhaled nitric oxide and blood eosinophil count, and nasal polyps with eosinophil infiltration in bilateral nasal cavities. She was diagnosed with eosinophilic airway inflammation and ECRS, and treated with corticosteroid inhalation, steroid nasal spray, and nasal irrigation, resulting in symptom reduction. Although they are relatively rare irAEs of ICIs, clinicians should consider these diseases associated with T2 inflammation and treat appropriately. Abstract : There are many immune‐related adverse events (irAEs) induced by immune checkpoint inhibitors; however, irAEs associated with type 2 inflammation are less known. We report a case of eosinophilic airway inflammation and eosinophilic chronic rhinosinusitis simultaneously during combination therapy with nivolumab and ipilimumab for renal cell carcinoma.